Analisis Ketahanan Material Lance Tube Sootblower Tipe 2 IK Superheater Desain Sendiri Dengan Perbandingan Material Desain Perusahaan Di PLTU Suralaya Unit 1-4 - Andika Widya p; Gita Puspa Artiani; Reza Alfin (JURNAL POWERPLANT, 2016)
Power Plant is a type of thermal power plant that is widely used, because of its fuel efficiency is good and easily obtained thus producing electrical energy economically.One Supporting Components Boiler ie Furnace, Steam Drum, Superheater, Water Heater, economizer, Safety Valve, Sootblower. Sootblower a boiler auxiliary equipment which serves to clean the dirt produced from the combustion process that is attached to the tube wall pipes, superheater, reheater, economizer, and water heater. The goal is to keep the heat transfer takes place properly and effectively. Long Retractable type Sootblower placed in superheater, Reheat, and economizer. This type is on stand-by condition is outside, and when the work will go spinning and turning it back out. if on the flue gas temperature is still very high, causing Sootblower bent by heat if it is not pulled out.